Antibacterial Production by Endophytic Bacteria from Catharanthus roseus in East Timor Against Methicillin-Resistant Staphylococcus aureus - Missa, Hildegardis; Ndukang, Sardina; Djalo, Aloysus; Nau, Getrudis W.; Susilowati, Ari; Baunsele, Anselmus Boy; Santos, Americo Dos (Universitas Negeri Semarang, 2024)
Methicillin-resistant Staphylococcus aureus (MRSA) refers to a group of bacteria that cause infections and present a challenge in treatment due to their resistance to several antibiotics. Therefore, research is needed to discover endophytic bacteria from Catharatus roseus capable of producing new antibiotics. This study aims to identify endophytic bacteria from C. roseus plants originating from Timor Island, as producers of effective antibacterial compounds against MRSA. Antibacterial activity tests were conducted on two types of test bacteria, namely MRSA and Escherichia coli. DNA extraction was performed using the PrestoTM Mini dDNA kit Bacteria, and amplification of the 16S rRNA gene was carried out. The research found bacterial isolates showing morphological similarities to Bacillus sp. Screening results indicated that four bacterial isolates exhibited high potential antibacterial activity against MRSA, as evidenced by the formation of inhibition zones with diameters of approximately 25 mm-35 mm. Amplification of the four endophytic bacterial isolates from C. roseus identified them as Paenibacillae FaCH2, Bacillae BoCH3, Aneurinibacillae BoCH5, Aneurinibacillae BiCH8, which are new species based on 16S rRNA gene similarity of less than 97%. In conclusion, endophytic bacteria from C. roseus producing antibacterial compounds against MRSA have been successfully identified. This is beneficial to society because the antibacterial compounds produced can serve as a basis for developing new drugs that are effective against MRSA infections, considering the increasing antibiotic resistance against MRSA.